Diversity of Mangrove Plant Species Used as Food Resources by the Community in Lalombi Village - Asnawar Asnawar; Samsurizal M Suleman; Moh Sabran; Musdalifah Nurdin; Vita Indri Febriani; Abd Hakim Laenggeng (Biology, Medicine, & Natural Product Chemistry, 2026)
Mangroves are distinctive plants that grow in coastal areas, estuaries, river mouths, and sheltered deltas in tropical and subtropical regions. The economic value of mangrove plants lies in their wood and fruit. This study aimed to identify the potential of mangrove plants as food resources in Lalombi Village. The research employed observation, interviews, and questionnaire distribution to local communities. The results revealed that five mangrove species are utilized as food resources, namely Avicennia marina (Forsk.) Vierh., Nypa fruticans Wurmb, Bruguiera gymnorhiza (L.) Lamk., Acanthus ilicifolius L., and Sonneratia alba. These species are processed into various food products, including mangrove onde-onde, mangrove syrup, mangrove crackers, mangrove tea, and mangrove dodol. The processing methods involve traditional techniques such as soaking, boiling, filtering, pounding, drying, and packaging. Questionnaire results indicated that the local community possesses a very good level of knowledge and positive perceptions regarding the potential of mangroves as food resources and sources of economic income. Support from the government and non-governmental organizations (NGOs) was considered beneficial, although challenges remain in terms of technology, marketing, and product legalization. This study recommends the provision of further training, policy support, and the promotion and sustainable development of mangrove-based products to enhance the welfare of coastal communities.